Assessment of Qibla Direction Accuracy at Tanwir Mosque, Surabaya,Using Theodolite Measurements - Alfira Rahma Fauziah (Astroislamica: Journal of Islamic Astronomy, 2025)
Every Muslim is obliged to perform the five daily prayers, the validity of whichis contingent upon the fulfillment of several essential conditions, one of which is observing the prescribed prayer times. In addition, the orientation toward the Qibla constitutes a fundamental requirement that must be determined accurately based on geographical location. Regions situated to the east of the Kaaba are required to face westward in determining the Qibla direction, and conversely, regions located to the west must face eastward. This study aims to examine the accuracy of the Qibla direction at the Tanwir Mosque in Surabaya using a theodolite. The research employed a field-based observational method to obtain precise empirical data. The theodolite, as a modern surveying instrument, is widely recognized for its high level of precision in angular measurements. The findings indicate that minor discrepancies exist among measurements obtained using different instruments; however, these differences remain within acceptable tolerance limits. Compared to other measurement tools, the theodolite demonstrates the highest degree of accuracy. This research is significant in ensuring the correctness of the Qibla direction and in enhancing public awareness regarding the importance of precision in the performance of religious worship.